Lupus-Like Syndrome Caused by 5-Aminosalicylic Acid in Patients with Inflammatory Bowel Disease - Andrew W Kirkpatrick; Arthur A Bookman; Flavio Habal (Canadian Journal of Gastroenterology)
BACKGROUND: Although 5-aminosalicylic acid (5-ASA) preparations used to treat inflammatory bowel disease are reported to have fewer side effects than sulphasalazine, increased clinical use of these compounds has resulted in increased reports of significant side effects.